The life of Saint Paraskeva-Petka of Tarnovo in „Berlin Damaskin”. The genological and thematic aspect - Kuczyńska, Marzanna (Balcanica Posnaniensia. Acta et studia, 2023)
The subject of interest in the article is the eighteenth-century New Bulgarian version of the Hagiography of Saint Paraskeva-Petka of Tarnovo by the Bulgarian Patriarch Euthymius (14th century), included in the poorly researched „Berlin Damaskin” currently stored in the Jagiellonian Library in Krakow (the so-called Berlin Collection) under the reference number Berol. Ms. Slav. fol. 36; cards 180–187v. The analysis concerns the genological and thematic aspect of the manuscript in the context of the ‘damaskin’ literature (Bulg. дамаскини) of the 16th–18th centuries. The main attention is focused on the content of the text, rhetorical-stylistic transformation (reduction, lowering of style) of the original and its new components. The most interesting element of the structure are the textological additions related to the journey of Paraskeva’s relics from Bulgaria through Serbia to Greece and Moldova, which make it possible to include the Krakow variant of the Petka Life in the Moldovan hagiographic redaction.